Study on the coupling coordinated development of ecological environment and industrial economy in the Russian Far East Federal District - Chu, Nanchen; Huang, Xiwen; Zhang, Pingyu; Tuo, Zhili (Frontiers in Environmental Science, 2025)
Under the background of the international development trend, the Russian Far East Federal District has become the open frontier area of the comprehensive strategic cooperation between China and Russia, which possesses great research value. Focusing on the Russian Far East Federal District as the study object, this paper constructs the ecological environment evaluation system and the industrial economic evaluation system. Combined with the comprehensive weighting method of the entropy weighting method and coefficient variation weighting method, this paper quantitatively calculates the ecological environment levels and the industrial economy levels in the Russian Far East Federal District from 2017 to 2023. Based on the coupling coordination model, this paper quantitatively analyzes the degree, characteristics and dynamic evolution of the coupling coordinated development of the ecological environment levels and the industrial economy levels in the Russian Far East Federal District from 2017 to 2023. The results show that from 2017 to 2023, in the Russian Far East Federal District, 1) In the ecological environment system, the ecological environment levels generally show the trend of first rising and then declining, showing the pattern characteristics of “High West, Low East” and “High South, Low North”. 2) In the industrial economic system, the industrial economic levels generally show the increasing trend, showing the pattern characteristics of “High Core, Low Northeast and Low Southwest”. 3) The coupling coordinated development degree of industrial economy and ecological environment shows the increasing trend, but it is still in the basic coordinated stage in general, which is characterized by the unbalanced pattern of “High Northwest, High Southeast, Low Northeast and Low Southwest”. Finally, the proposals for the coordinated development of the ecological environment and industrial economy are proposed in the Russian Far East Federal District.